High revision rates with the metal-on-metal Motec carpometacarpal joint prosthesis. (March 2016) - Thillemann, J. K.; Thillemann, T. M.; Munk, B.; Krøner, K.
We retrospectively evaluated a consecutive series of 42 Motec thumb carpometacarpal total joint arthroplasties. The primary endpoint was revision with implant removal and trapeziectomy. At follow-up the disability of the arm shoulder and hand (DASH) score, pain on numerical rating scale at rest and with activity and serum chrome and cobalt concentrations were assessed for both unrevised and revised patients. At a mean follow-up of 26 months, 17 patients had been revised. The 2 year cumulative revision rate was 42% (95% CI, 28–60%). The DASH score and pain scores at rest and with activity were comparable between the patients whose thumbs remained unrevised and those revised. Patients with elevated serum chrome and cobalt levels had significantly higher DASH and pain scores, but elevated levels were not associated with revision. The revision rate in this study is unacceptably high. However, pain and DASH scores after revision are acceptable and comparable with patients with non-revised implants. Level of evidence: IV